Pembuatan Website Company Profile Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Samarinda - Landika Bramasta Erlian Susilo; M Arif Budiman S; Muhammad Fadly Ramadhani; Rezqi Syayuwan; Muhammad Taufiq Sumadi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
In the era of globalization, the development of information technology services has grown quite rapidly in various aspects of life. Information technology has developed along with human abilities, which has created technologies that are more sophisticated and practical in helping human life. Examples of technology that have developed include machines, communication tools, and so on. This development does not only occur in urban areas but also in rural areas where information service technology has made it easier for people to access various information. The Samarinda City Women's Empowerment and Child Protection Service is committed to always being transparent in its implementation, especially in information regarding the Samarinda City Women's Empowerment and Child Protection Service. Therefore, the service team wants to create a WordPress Content Management System (CMS) based media website which contains information related to the Samarinda City Women's Empowerment and Child Protection Service. The method that the author will use in this service is how to manage a website properly and correctly. The aim of this community service is to create a website profile related to the Samarinda City Women's Empowerment and Child Protection Service and to make it easier for people who want to find information about the Samarinda City Women's Empowerment and Child Protection Service. The final result of this service is the Company Profile Website for the Samarinda City Women's Empowerment and Child Protection Service.